Oh, the Places We’ll Go: Patient-Reported Outcomes and Electronic Health Records - Gensheimer, Sarah G.; Wu, Albert W.; Snyder, Claire F. (The patient : patient-centered outcomes research, 2018)
The growing measurement of patient-reported outcomes (PROs) and adoption of electronic health records (EHRs) presents an unprecedented opportunity to improve health care for patients and populations. The integration of PROs into EHRs can promote patient-centered care and advance quality improvement initiatives, research, and population health. Despite these potential benefits, there are few best practices to help organizations achieve integration. To integrate PROs into EHRs, organizations should evaluate the advantages and disadvantages of various approaches within three themes: Planning, Selection, and Engagement. Planning considerations for integration include what strategy will be used, how the integrated system will be governed, ethical and legal issues, and how data from multiple EHRs can be pooled across organizations. Selection considerations involve identifying which patient population to target for PRO data collection on the basis of the intended use of the data in the health care system, and then choosing specific outcomes and their measures. Engagement considerations include how, where, and with what frequency patients will respond to PRO measures, how to display PRO data in EHRs, how clinical teams will act upon PRO data, and how to train, support and incent clinical teams and patients to incorporate PRO data into care. There is no most effective model that will work in all contexts. Organizations wishing to integrate PROs and EHRs should assemble the multidisciplinary expertise needed to evaluate the advantages and disadvantages of the various approaches for their particular context. We specifically recommend that organizations think carefully about stakeholder participation; design their system with data sharing in mind; develop a framework to aid in PRO selection; create guidelines to support PRO interpretation and action for patients and clinicians; and ensure patients have access to their own PRO data.